2014
DOI: 10.1021/jp5060974
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Performance of Duolayers at the Air/Water Interface. 1. Experimental Analysis

Abstract: Understanding, and improving, the behavior of thin surface films under exposure to externally applied forces is important for applications such as mimicking biological membranes, water evaporation mitigation, and recovery of oil spills. This paper demonstrates that the incorporation of a water-soluble polymer into the surface film composition, i.e., formation of a three-duolayer system, shows improved performance under an applied dynamic stress, with an evaporation saving of 84% observed after 16 h, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The morphology and homogeneity of Chp F Langmuir films at pH 3.0 or 10.0 at the air/water interface was visualized using a Brewster angle microscope (BAM, KSV NIMA, Biolin Scientific, Västra Frölunda, Sweden) mounted on a Langmuir trough (KN 2003, KSV NIMA). The BAM was equipped with a 50 mW laser emitting p-polarized light with a wavelength of 658 nm, which was reflected off the air/water interface at the Brewster angle (~53°) [ 40 ]. The lateral resolution of the microscope was 2 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology and homogeneity of Chp F Langmuir films at pH 3.0 or 10.0 at the air/water interface was visualized using a Brewster angle microscope (BAM, KSV NIMA, Biolin Scientific, Västra Frölunda, Sweden) mounted on a Langmuir trough (KN 2003, KSV NIMA). The BAM was equipped with a 50 mW laser emitting p-polarized light with a wavelength of 658 nm, which was reflected off the air/water interface at the Brewster angle (~53°) [ 40 ]. The lateral resolution of the microscope was 2 μm.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, canal viscometry experiments have shown that the duolayer has a greater surface viscosity than the monolayer, 19 which suggested it may be more stable under wind. This two-part (1 and 2) publication series aims to examine the dynamic performance of the duolayer systems experimentally (part 1) 20 and elucidate the molecular mechanisms of its behavior theoretically using all-atom NEMD simulations, presented herein (part 2). The experimental data on the dynamic performance of the three-monolayer and three-duolayer systems presented in part 1 of this two-part series 20 show that, under wind conditions, not only does the duolayer outperform the monolayer as an evaporation suppressant, but it also outperforms itself under stationary conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This two-part (1 and 2) publication series aims to examine the dynamic performance of the duolayer systems experimentally (part 1) 20 and elucidate the molecular mechanisms of its behavior theoretically using all-atom NEMD simulations, presented herein (part 2). The experimental data on the dynamic performance of the three-monolayer and three-duolayer systems presented in part 1 of this two-part series 20 show that, under wind conditions, not only does the duolayer outperform the monolayer as an evaporation suppressant, but it also outperforms itself under stationary conditions. Here, we use classical molecular dynamics techniques to compare the interfacial properties of the monolayer and duolayer systems under equilibrium and applied force conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations